A Zinc Finger Transcriptional Repressor Confers Pleiotropic Effects on Rice Growth and Drought Tolerance by Down-Regulating Stress-Responsive Genes. (18th July 2018) - Yuan, Xi; Huang, Peng; Wang, Ruqin; Li, Haoyuan; Lv, Xueqing; Duan, Min; Tang, Haijuan; Zhang, Hongsheng; Huang, Ji
Abstract: The C2H2-type zinc finger proteins (ZFPs) are involved in a wide range of plant development and stress responses. Many studies have shown the positive roles of ZFP genes in stress tolerance. However, overexpression of ZFP genes usually leads to the side effect of growth retardation. Here we report a new member of the ZFP family, Oryza sativa drought-responsive zinc finger protein 1 (OsDRZ1), positively regulating both stress tolerance and plant architecture in rice ( Oryza sativa L.). OsDRZ1 was expressed throughout all tissues examined and could be induced by multiple abiotic stresses. OsDRZ1 protein was localized mostly in the nucleus. Unlike most reported rice ZFPs functioning as transcriptional activators, OsDRZ1 is a transcriptional repressor. Overexpression of OsDRZ1 in rice increased seedling drought tolerance and the transgenic plants appeared to accumulate more free proline and fewer reactive oxygen species (ROS), and elevate the activities of antioxidant enzymes. In contrast, RNA interference (RNAi) of OsDRZ1 led to lower activities of antioxidative response and more sensitivity to drought. RNA sequencing analysis revealed that the genes down-regulated by OsDRZ1 were mostly down-regulated by drought, implying the critical role of OsDRZ1 in modulating drought-responsive gene expression. A cupin gene OsGLP1 ( germin-like protein1 ) was identified as one of the potential target genes of OsDRZ1, as suggested by real-time PCR and transient expression analysis in rice protoplasts. Moreover, overexpression of OsDRZ1 did not lead to growth inhibition but the promotion of rice growth, implying the potential application prospective of OsDRZ1 in engineering drought-tolerant crops.